Influence of the ye'elimite/anhydrite ratio on PC-CSA hybrid cements. (March 2020) - Bolaños-Vásquez, I.; Trauchessec, R.; Tobón, J.I.; Lecomte, A.
Abstract: Portland cement (PC) and Calcium sulfoaluminate cement (CSA) blends are used to produce binders with properties as rapid hardening. However, characteristics of calcium sulfoaluminate cements such as chemical and mineralogical composition, particle size distribution, among others, can have an enormous variation and affect the performance of the PC-CSA cement mixture. Therefore, current research focus on the mechanical properties and hydration of PC-CSA (75 wt%-25 wt%) blend cement using three different CSA cements in order to better understand the influence of property variations like ye'elimite quantity and ye'elimite/anhydrite ratio in CSA cements on PC-CSA systems. Compressive strength was determined on mortars and hydration was studied on paste using isothermal calorimetry, X-ray diffraction and thermal analysis. Results showed that ye'elimite quantity in CSA used into PC-CSA hybrid cements have a large influence in early hardening and hydration. But, beyond the quantity of ye'elimite, findings showed that there is a greater influence of the ye'elimite/anhydrite ratio on the heat release, mineralogy and compressive strength of PC-CSA blends. For example, it was found that it is necessary to adjust the sulfate content to avoid compressive strength stagnation. Higher ye'elimite/anhydrite yields to higher mechanical strengths independent on the type of CSA.